Impact of Inlet Partition Distance on Broiler Carcass Quality in Closed House Production Systems - Rizqon Fadhitya Anugerah; Catur Suci Purwati (Jurnal Biologi Tropis, 2026)
The significance of environmental management in closed-house systems is discussed in this paper, with a focus on the function of partition location in preserving ideal microclimate conditions for broiler production. The growth performance and carcass quality of broiler chickens may be impacted by uneven temperature distribution caused by improper partition distances. This study examined how the carcass quality of broiler chickens in a closed-house system was affected by partition distances from the intake (P1: 0 m, P2: 30 m, and P3: 60 m). Partition location had a substantial impact on carcass weight, carcass percentage (P<0.01), and belly fat (P<0.05), according to an analysis of 36 male broilers. Due to heat buildup in the intermediate zone, P2 had the lowest carcass weight (2059.15 g), whereas P1 and P3 had the greatest (2234.03 g and 2207.88 g). Because of the best airflow close to the blower and effective energy conversion, P3 had the greatest carcass percentage (77.5%) and belly fat (1.9%). The study comes to the conclusion that partition distance modifies the microclimate of the home, which has a direct impact on the performance of broiler production.